PERANCANGAN GAME EDUKATIF TENSES MATCH-UP BERBASIS INTERAKTIF MENGGUNAKAN SCRATCH DI MAS DARULMUTA’ALLIMIN BLANG BINTANG - Salma Wati; Mira Maisura (Badan Penelitian dan Pengabdian Masyarakat (BP2M) STMIK Syaikh Zainuddin NW Anjani, 2025)
Understanding tenses in English remains a common obstacle for many students, including those at MAS Darul Muta'allimin Blang Bintang. The lack of variety in learning methods leads to low student engagement in understanding these grammatical concepts. This study aims to design an interactive educational game titled Tenses Match-Up based on Scratch, as an interesting and communicative alternative learning medium. The method used is Research and Development (R&D) with the Alessi and Trollip development model which includes the planning, design, and development stages. The game is designed with three main modes, namely Drag the Tense, Sound and Sense, and Pause and Sense, which are adapted to four main types of tenses: simple present, simple past, simple future, and present perfect. Validation was carried out by media experts and material experts to assess visual quality, interactivity, and content suitability. The validation results showed that this media was declared very suitable for use with a suitability percentage of 91.66% and 83.33%, respectively. Although it has not been tested directly on students, these results suggest that the educational game Tenses Match-Up has the potential to support more engaging and effective English learning at the high school level